THE INFLUENCE OF E-SERVICE QUALITY AND PERCEIVED QUALITY ON CONSUMER LOYALTY OF ONLINE SHOP TOKOPEDIA USERS IN MALANG CITY - Wisaksana, Albar Rizaldy (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2020)
The purpose of this study is to determine the effect of e-service quality and perceived quality on consumer loyalty of online shop users (research on Tokopedia) in Malang. This research is a research study with quantitative analysis using path analysis or commonly referred to as descriptive analysis. Data was collected through an online survey using a questionnaire instrument with responses that can be used from 100 respondents who use Tokopedia's online shop. The results of this study service quality and perceived quality in this study provide significant results on consumer loyalty. Future studies are expected to develop this research variable by adding independent variables namely Behavioral Intentions or directly to the Word of Mouth, Site Revisit, and Purchase Intention indicators.Keywords: E-service quality, perceived quality, consumer loyalty